Developing guidelines on EFT for same‐sex/gender relationships: Recommendations from a Delphi study. - Edwards, Caitlin; Wittenborn, Andrea K.; Allan, Robert (Family Process, 2025)
Emotionally focused therapy (EFT) is one of few empirically supported treatments for relationship distress. While evidence‐based approaches are critical for ensuring safe and effective treatment, EFT has not been adapted for use with same‐sex/same‐gender (SS/SG) relationships. This study used the Delphi method to generate consensus on treatment guidelines for using EFT with SS/SG relationships. Forty therapists with clinical expertise in EFT for SS/SG relationships were recruited. Data were collected in three phases. In phase one, participants responded to open‐ended questions regarding how EFT should be adapted for SS/SG relationships. Phases two and three involved participants rating the importance of the recommended guidelines. Data were analyzed using thematic analysis and descriptive statistics. The final recommendations included 49 guidelines on EFT for SS/SG relationships. The data reflected modifications to therapists' foundational knowledge and development, practice set up and orientation, and the three stages and nine steps of EFT.